The characteristic of eruption of Indonesian active volcanoes in the last four decades - Akhmad Zaennudin (Jurnal Lingkungan dan Bencana Geologi, 2010)
Indonesia has 129 active volcanoes those are scattered in Sumatra, Java, Bali, Nusa Tenggara, Maluku, and Sulawesi islands. Approximately 13% of the world’s active volcanoes are located in Indonesia. Active volcano in Indonesia is divided into three categories, namely type A, B, and C. A type are those volcanoes recorded eruption since 1600. B type volcanoes are those in solfataric and or fumarolic activity, there is crater since the year 1600 there is no evidence of increasing activity nor eruption. Type C are volcanoes those are in solfataric stage and or occasionally the volcanic edifice is not clear. There are 79 active volcanoes that consist of type A, 29 volcanoes type B, and 21 volcanic type C.“A type volcano” is the first priority for our institution to monitor their activities. Each year approximately 10 to 12 active volcanoes in Indonesia increase their activity, and two to four volcanoes erupted with different characters. At least there are five characters of volcanic eruption of Indonesian active volcanoes that can be recognized in the last four decades. The first character are volcanoes with lava domes; the second are those with crater lakes; the third are those with open vent system; the fourth with gas eruption, and the fifth are cones inside a caldera.Keywords: character of volcanic eruption, solfataric, fumarolicSARIIndonesia mempunyai 129 gunung api aktif yang tersebar mulai Sumatera, Jawa, Bali, Nusa Tenggara, Sulawesi dan Maluku. Jumlah tersebut sama dengan 13% gunung api aktif di dunia. Gunung api aktif Indonesia dibedakan dalam 3 kategori berdasarkan sejarah letusannya, yaitu gunung api tipe A, tipe B, dan tipe C. Gunung api tipe A tercatat pernah meletus sejak 1600, jumlahnya 79. Tipe B adalah gunung api yang mempunyai kawah dan lapangan solfatara/fumarola tapi tidak ada sejarah letusan sejak tahun 1600, jumlahnya 29. Gunung api tipe C hanya berupa lapangan solfatara/fumarola, jumlahnya 21. Gunung api tipe A yang diprioritaskan untuk diamati. Setiap tahun antara 10 sampai 12 gunung api yang meningkat aktivitasnya, yang mencapai tahap letusan sebanyak 2 sampai 4 dengan karakter yang berbeda. Paling sedikit ada 5 karakter letusan gunung api di Indonesia yang diamati dalam empat dekade terakhir, yaitu letusan yang menghasilkan kubah lava, letusan dari danau kawah, ketiga letusan dengan in pipa (kepundan) yang terbuka, keempat adalah letusan gas, dan yang ke lima adalah letusan yang menghasilkan bukit baru di dalam kaldera.Kata kunci: karakter letusan gunung api, solfatara, fumarola